2016
DOI: 10.1093/eep/dvw006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ambient particle exposures and blood DNA methylation age: findings from the VA normative aging study

Abstract: BackgroundAmbient particles have been shown to exacerbate measures of biological aging; yet, no studies have examined their relationships with DNA methylation age (DNAm-age), an epigenome-wide DNA methylation based predictor of chronological age.ObjectiveWe examined the relationship of DNAm-age with fine particulate matter (PM2.5), a measure of total inhalable particle mass, and black carbon (BC), a measure of particles from vehicular traffic.MethodsWe used validated spatiotemporal models to generate 1-year PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 69 publications
7
62
1
Order By: Relevance
“…Horvath DNAm-age is a tissue-independent predictor of chronological age that is calculated from DNA methylation values at 353 chronological age-correlated CpG dinucleotides in Illumina’s HumanMethylation450 BeadChip (Horvath, 2013). Specifically, in an elderly cohort and with fully-adjusted models, we observed that a 1 μg/m 3 increase in 1-year PM 2.5 exposure was associated with a 0.52-year increase in Horvath DNAm-age (Nwanaji-Enwerem et al, 2016). …”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Horvath DNAm-age is a tissue-independent predictor of chronological age that is calculated from DNA methylation values at 353 chronological age-correlated CpG dinucleotides in Illumina’s HumanMethylation450 BeadChip (Horvath, 2013). Specifically, in an elderly cohort and with fully-adjusted models, we observed that a 1 μg/m 3 increase in 1-year PM 2.5 exposure was associated with a 0.52-year increase in Horvath DNAm-age (Nwanaji-Enwerem et al, 2016). …”
Section: Introductionmentioning
confidence: 84%
“…We then generated 1-year total PM 2.5 and PM 2.5 component species exposure windows by averaging daily exposures for the 365 days prior to the day of each participants’ NAS visit. The 1-year PM 2.5 exposure window was utilized because it has been previously reported to be robustly associated with DNAm-age (Nwanaji-Enwerem et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study of epigenetic biomarkers of aging and air pollution using the NAS cohort observed positive associations between the epigenetic biomarkers and both PM 2.5 and BC [34]. Our analysis included additional epigenetic aging biomarkers (e.g.…”
Section: Discussionmentioning
confidence: 99%